Mainstreaming One Health - Zinsstag, J.; Mackenzie, John; Jeggo, M.; Heymann, D.; Patz, J.; Daszak, P. (Springer New York LLC, 2012)
The term ‘One Medicine’ was coined by Schwabe (1984) and focuses attention on the commonality of human and animal health. The underlying concept is traceable to the late nineteenth century, in contributions of the German pathologist and architect of social medicine Rudolf Virchow (Saunders 2000; Zinsstag and Weiss 2001). Schwabe states that there is no difference in paradigm between human and veterinary medicine and that both medicines have the same scientific foundations. Yet, human and animal health developed during the nineteenth and twentieth centuries into fairly segregated disciplines or ‘silos’, separated at the academic, governance and application levels. In recent decades, the concept of ‘One Medicine’ evolving to ‘One Health’ has gained momentum worldwide after the SARS outbreak in 2003, and then driven by fears of a possible pandemic of H5N1 avian influenza (Zinsstag et al. 2005; Worldbank 2010). One Health now encompasses a broad agenda from zoonotic infections (Roth et al).